RENEWABLE ENERGY CERTIFICATES: APPLICATION POTENTIAL AND EFFIENCY - M. M. Balashov (Стратегические решения и риск-менеджмент, 2020)
At the international level, the problem of the need to increase the contribution of renewable energy sources to domestic electricity demand is highly relevant. Since the production of renewable energy sources is quite expensive, many countries are developing various state and market incentives for investment in such energy sources. One such incentive is renewable energy certificates. The role of these certificates in the development of global renewable energy markets is invaluable. They not only help businesses achieve their goals in the field of renewable energy, but also reduce consumer payments for other renewable energy development programs. This article analyzes the current trends in the use of renewable energy certificates in the world and identifies the prospects for their use in the Russian Federation. In addition, the author of the article studied the issue of cost-effectiveness of renewable certificates. In order to assess the positive economic impact of the application of the certification system, calculations have been made to reduce the financial burden on participants in the Wholesale Electricity and Power Market by taking into account the funds received from the sale of these certificates to reduce payments by market participants to generators based on renewable sources under the program of agreements on the provision of capacity for generating objects operating on the basis of renewable energy sources, from the date of the start of supply of electric energy and of the last planned facility until the date of the last payment under the power capacity agreement. In addition, the author of the article studied the need for renewable energy certificates not only to obtain reliable data on the use of renewable energy sources, but also to create efficient electricity markets using renewable energy sources around the world.